Three sixty five days - Blanka, Lipinska (London Simon and Schuster, 2021)
Laura Biel and her boyfriend are on a dream vacation in beautiful Sicily. On the second day of their trip, her twenty-ninth birthday, she is kidnapped. Her kidnapper is none other than the head of a powerful Sicilian crime family, the incredibly handsome, young Don Massimo Torricelli, who is determined to possess her at all costs. Massimo has his reasons. During an earlier attempt on his life, a vision appeared before his eyes: a beautiful woman, identical to Laura. After surviving the attack, he vows that he will find the woman in his vision and make her his own. No matter what.For 365 days, Massimo will keep Laura captive in his palatial estate and attempt to win her heart. If she doesn$1 (Bt fall in love with him during this time, he will let her go. But if she tries to escape at any point, he will track her down and kill her entire family.Soon Laura develops a fascination with her handsome and powerful captor. But as a precarious, risky relationship forms between them, forces outside their control threaten to tear them apart..s
Keywords: Polish